2022
DOI: 10.1002/mc.23468
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Nrf2 binds to circRNAPIBF1 to regulate SOD2 in lung adenocarcinoma progression

Abstract: Emerging evidence indicates that circular RNAs (circRNAs) play important roles in disease development, especially in cancers. Analysis of circRNA expression microarrays from the Gene Expression Omnibus database revealed that circPIBF1 was highly upregulated in lung adenocarcinoma (LUAD). The main aim of this study was to probe the function of circPIBF1 in pyroptosis of LUAD cells and the signal transduction pathways involved. CircPIBF1 was significantly overexpressed in LUAD and was related to the dismal progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It has been reported that circRNA expression is regulated by transcription factors 18–20 . To identify the upstream mechanisms of circCASK, we explored the NCBI (https://www.ncbi.nlm.nih.gov/), UCSC (http://genome.ucsc.edu/), and JASPAR (http://jaspar.genereg.net/) datasets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that circRNA expression is regulated by transcription factors 18–20 . To identify the upstream mechanisms of circCASK, we explored the NCBI (https://www.ncbi.nlm.nih.gov/), UCSC (http://genome.ucsc.edu/), and JASPAR (http://jaspar.genereg.net/) datasets.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we further investigated the upstream mechanisms of circCASK by exploring potential transcription factors that could regulate circRNAs expression in various cells 18–20 . By generating knockdown or overexpression cell models, we found that FOXC2 positively regulated circCASK expression in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether the increase in established NFE2L2/NRF2-regulated transcripts measured in Wdr23KO hippocampus resulted in an increase in steady state abundance of stress adaptation proteins, we quantified the steady state level of several proteins with roles in redox and oxidative stress resistance [45]. We noted an increase in the abundance of several proteins that mediate survival and protection from oxidative stress [46] in the Wdr23KO relative to WT; these include the glutathione peroxidase 4 (GPX4, Figure 6A-B ), glutathione S transferase 4 (GSTA4, Figure 6A,C ), aldehyde dehydrogenase 2 (ALDH2, Figure 6A,D ), and the manganese superoxide dismutase 2 [47] (SOD2, Figure 6E-F ). Intriguingly, we could not detect an increase in all proteins with known sensitivity to NFE2L2/NRF2 activation (Figure S6) suggesting a failure in the sensitivity of detection for these proteins or perhaps specificity to the WDR23-axis of regulation of NFE2L2/NRF2 in the hippocampus specifically, which will be of great future interest.…”
Section: Resultsmentioning
confidence: 99%